Synovial sarcoma extracellular vesicles induce fatty liver - Ren, Tao; Zhou, Zhiheng; Hong, Huirong; Cen, Bohong; Xiao, Jun; Chen, Guofen; Zhang, Yang; Li, Jianlong (Biophysics reports, 2025)
Synovial sarcoma leads to pathological changes in multiple organs. To investigate the mechanism by which synovial sarcoma induces fatty liver through extracellular vesicles (EVs), the synovial sarcoma SW-982 cells were orthotopically implanted, or SW-982 derived EVs were extracted and used to "educate" nude mice. Liver tissues were then subjected to H&E and Oil-Red O (ORO) staining, and qPCR analysis. EVs were characterized using TEM and Nanosight. The bio-distribution of EVs was verified using the fluorescent dye Burgundy staining, followed by Odyssey imaging. Immunofluorescence (IF) and flow cytometry were used to confirm cellular uptake of EVs. Rab27a knockdown (KD) efficiency was validated by Western blot, and lipid droplet deposition in the liver from mice bearing with SW-982-Rab27a-KD cells was observed by staining with ORO. After three weeks of orthotopic implantation of SW-982 cells in nude mice, qPCR and H&E showed no tumor metastasis in liver tissues, while ORO staining revealed lipid deposition in the liver, and EVs diameters were confirmed by Nanosight and TEM to be approximately 141 nm in size. , EVs were taken up by liver Kupffer cells (KCs). After "educating" nude mice with EVs, lipid deposition in the liver was observed. In rescue experiments, Rab27a knockdown reduced EV secretion from the tumor, and KC inactivation led to decreased lipid deposition in the liver. It is shown that synovial sarcoma EVs mediate fatty liver through Kupffer cells.